A distinctive new species of flowerpecker (Passeriformes: Dicaeidae) from Borneo - Saucier, Jacob R.; Milensky, Christopher M.; Caraballo-Ortiz, Marcos A.; Ragai, Roslina; Dahlan, N. Faridah; Edwards, David P. (Zootaxa, 2019)
The enigmatic ‘Spectacled Flowerpecker’—a probable new bird species from the island of Borneo—was first sighted in the Danum Valley of Sabah, Malaysia in 2009. However, the absence of a holotype specimen has prevented its formal scientific description. Since then only a handful of reports from widely disparate localities across the island have emerged, all from lowland sites and often in close association with fruiting mistletoe. Here, we report the long-awaited capture of a specimen of this putative new species and confirm its morphological and molecular distinctiveness as a novel species in the genus Dicaeum.